Bhutan's happiness mantra and values-based education - Abdul Razak, Dzulkifli (New Straits Times Press (M) Bhd., 2019)
A values-based education will inculcate spiritual values of kindness, equality, compassion and humanity, producing ‘genuine human beings’ who can realise their full and true potential.